2020
DOI: 10.1002/met.1872
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of sub‐daily ensemble precipitation forecasts

Abstract: Nowadays, major advances have been made in meteorological forecasts. For instance, ensemble forecast systems have been developed to quantify prediction uncertainty. In this research, sub‐daily ensemble precipitation forecasts of five THORPEX Interactive Grand Global Ensemble (TIGGE) models from 2014 to 2018 were evaluated in 10 major basins located in north and west Iran. Furthermore, Bayesian model averaging (BMA) was used to combine five prediction models and construct a grand ensemble. The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The THORPEX Interactive Grand Global Ensemble (TIGGE) datasets have been widely used for precipitation forecasts, which was established through The Observing System Research and Predictability Experiment (THORPEX) project. Several studies have assessed the effectiveness of TIGGE forecasts for meteorological and hydrological applications (Zhao et al 2011, Tao et al 2014, Louvet et al 2016, Liu et al 2019, Saedi et al 2020, Shu et al 2021. For instance, Zhao et al (2011) compared forecasts from different models including the European Centre for Medium-Range Weather Forecasts (ECMWF), the National Center for Environmental Prediction (NCEP), and the China Meteorological Administration (CMA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The THORPEX Interactive Grand Global Ensemble (TIGGE) datasets have been widely used for precipitation forecasts, which was established through The Observing System Research and Predictability Experiment (THORPEX) project. Several studies have assessed the effectiveness of TIGGE forecasts for meteorological and hydrological applications (Zhao et al 2011, Tao et al 2014, Louvet et al 2016, Liu et al 2019, Saedi et al 2020, Shu et al 2021. For instance, Zhao et al (2011) compared forecasts from different models including the European Centre for Medium-Range Weather Forecasts (ECMWF), the National Center for Environmental Prediction (NCEP), and the China Meteorological Administration (CMA).…”
Section: Introductionmentioning
confidence: 99%
“…They found that ECMWF exhibited better performance than the other models; however, the forecast skills of all models decreased significantly after five days of lead time. Many previous studies highlighted the favorable performance of the UK Meteorological Office (UKMO) and ECMWF models compared to other models (Saedi et al 2020). Bhomia et al (2017) reported that forecasts from UKMO, NCEP, and ECMWF demonstrated satisfactory performance for rainfall predictions and tropical cyclones in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and enhancement of numerical weather prediction (NWP) models have been increased considerably during the last decade. Therefore, the meteorological forecasts provide new opportunities for rainfall–runoff modelling and early warning issues (Cloke & Pappenberger, 2009; Gevorgyan, 2013; Saedi et al, 2020). One of the widely used data sets for extracting precipitation forecasts is the THORPEX (The Observing System Research and Predictability Experiment) Interactive Grand Global Ensemble (TIGGE), which is established through THORPEX project.…”
Section: Introductionmentioning
confidence: 99%
“…In India, Bhomia et al (2017) evaluated seven NWP models within the TIGGE for studying the tropical cyclones and found that the forecasts of UKMO, NCEP and ECMWF were closer to the ground‐gauge observations. Saedi et al (2020) assessed five NWP models' sub‐daily forecasts in 10 river basins located in the north and west of Iran. Findings depicted that in terms of rainfall prediction, the UKMO and ECMWF are the best ones, whereas in detecting rainy or non‐rainy days, the NCEP model outperformed other models.…”
Section: Introductionmentioning
confidence: 99%